Challenges in the Implementation of Criminal Law for Sexual Crime Cases in Indonesia - Anis Noviya (Journal of Adat Recht, 2025)
Sexual crimes are one of the most serious crimes and deeply affect the victims. In Indonesia, although there are various laws regulating the handling of sexual crimes, the implementation of criminal law in these cases faces various challenges. This study aims to explore and analyze the main challenges in the application of criminal law to cases of sexual crimes in Indonesia, using a qualitative approach. This research method includes in-depth interviews with legal practitioners, including police officers, prosecutors, judges, and non-governmental organizations that focus on sexual crime issues. In addition, this study also conducted an analysis of relevant case studies and legal documents. The data collected were analyzed using thematic analysis techniques to identify and categorize the main challenges faced in the implementation of criminal law. The results of the study indicate that the main challenges in the implementation of criminal law for cases of sexual crimes. This study concludes that in order to improve the effectiveness of the implementation of criminal law in cases of sexual crimes, reforms are needed that include increased coordination between institutions, special training for law enforcers, and changes in social perceptions of victims of sexual crimes. These recommendations are expected to help create a more responsive and fair criminal justice system for victims of sexual crimes in Indonesia